Half-count myocardial imaging on the D-SPECT camera: phantom validation and clinical agreement for perfusion and function - Sharon Gomez Villegas; Dea Dundara Debeljuh; Daniela Calcaterra; Ivan Pribanic; Lucia Leva; Federico Garrou; Andrea D’Alessio; Roberta Matheoud; Marco Brambilla (British Journal of Radiology, 2026)
Abstract Objectives To evaluate the accuracy of the Cadmium-Zinc-Telluride (CZT) D-SPECT (Spectrum Dynamics, Israel) system in quantifying left ventricle (LV) perfusion and function in 99mTc myocardial perfusion imaging (MPI) at half count statistics. Methods Segmental perfusion, extent and volume of a perfusion defect were evaluated in an anthropomorphic phantom simulating normal and pathological myocardial condition at the reference 1 million counts (Mc) and at reduced count statistics (0.8, 0.6, 0.4, 0.25Mc). Summed Stress Scores (SSS), Summed Rest Scores (SRS), Summed Difference Score (SDS), Total Perfusion Deficit (TPD), Ischemic Total Perfusion Deficit (ITPD) and Ejection Fraction were evaluated in 326 MPI patient studies, stratified on the classification of myocardial perfusion and LV ejection fraction (LVEF), at 1 and 0.5Mc statistics. Results In the phantom study, the count statistics did not affect mean perfusion and perfusion defect extent and volume down to 0.4Mc. In the patient study, high concordance was observed between datasets, with Kw values of 0.846 (SSS), 0.922 (SRS), 0.676 (SDS), and K values of 0.89 (TPD) and 0.70 (ITPD). Bland Altman analysis showed minimal bias and narrow limits of agreement for LVEF (-0.1%; -6.9% to 6.7%). Conclusions The study demonstrated the feasibility of a 50% count reduction for myocardial perfusion imaging performed with the D-SPECT system and the acquisition/reconstruction protocol evaluated in this study, preserving diagnostic accuracy while lowering radiation exposure or acquisition time. Advances in knowledge The ability to maintain diagnostic accuracy with 50% fewer counts supports the adoption of optimized, low-dose SPECT protocols enhancing patient safety and imaging efficiency. This reinforces the role of CZT technology in low-dose nuclear cardiology.